From Transcriptomics, Metabolomics to Functional Studies: Extracellular ATP Induces TGF-β-Like Epithelial Mesenchymal Transition in Lung Cancer Cells - Evers, Maria; Song, Jingwen; Shriwas, Pratik; Greenbaum, Harrison S.; Chen, Xiaozhuo (Frontiers in Oncology, 2022)
We and others previously showed that extracellular ATP (eATP) is implicated in epithelial mesenchymal transition (EMT). However, the mechanisms by which eATP induces EMT and ATP’s relationship to TGF-beta, a well-known EMT inducer, are largely unclear. Also, eATP-induced EMT has never been studied at transcriptomic and metabolomics levels. Based on our previous studies, we hypothesized that eATP acts as a specific inducer and regulator of EMT at all levels in cancer cells. RNAseq and metabolomics analyses were performed on human non-small cell lung cancer (NSCLC) A549 cells treated with either eATP or TGF-beta. Bio-functional assays, such as invasion, intracellular ATP, cell proliferation, cytoskeleton remodeling, and others were conducted in NSCLC A549 and H1299 cells to validate changes observed from RNAseq and metabolomics studies. In the RNAseq study, eATP significantly enriched expressions of genes involved in EMT similarly to TGF-beta after 2 and 6 hours of treatment. Samples treated with eATP for 2 hours share 131 upregulated EMT genes with those of TGF-beta treated samples, and 42 genes at 6 hours treatment. Eleven genes, with known or unknown functions in EMT, are significantly upregulated by both inducers at both time points, have been identified. BLOC1S6, one of the 11 genes, was selected for further study. eATP induced numerous EMT-related changes in metabolic pathways, including cytoskeleton rearrangement, glycolysis, glutaminolysis, ROS, and individual metabolic changes similar to those induced by TGF-. Functional bioassays verified the findings from RNAseq and metabolomics that eATP EMT-like changes in A549 and H1299 cells similarly to TGF-beta. BLOC1S6 was found to be implicated in EMT. In these studies, eATP-induced EMT, at all levels examined, is similar but non-identical to that induced by TGF-beta and functions in such a way that exogenous addition of TGF-beta is unnecessary for the induction. The study of BLOC1S6 further verified its potential roles in EMT and the RNAseq analysis results. All these strongly indicate that eATP is a multi-functional and multi-locational inducer and regulator of EMT, changing our thinking on how EMT is induced and regulated and pointing to new directions for inhibiting EMT in cancer.